Antidiabetic Effect of Rehmanniae Radix Based on Regulation of TRPV1 and SCD1 - Ye Liu; Ruizheng Zhu; Bei Liu; Bei Liu; Wuqing Wang; Ping Yang; Zhonglian Cao; Xiaolei Yang; Wandi Du; Qing Yang; Jingru Liang; Jiarong Hu; et al. (Frontiers Media S.A., 2022)
Purpose: This study aimed to disclose the antidiabetic mechanisms of Rehmanniae Radix (RR).Methods: The antidiabetic effect of RR was studied in Streptozocin (STZ)-induced diabetes mellitus (DM) rats and HepG2 cells with insulin resistance (IR). Antidiabetic targets and signaling pathways of RR were confirmed by the network pharmacology and transcriptome analysis as well as HK2 cells induced by high glucose (HG).Results: After the DM rats were administrated RR extract (RRE) for 4 weeks, their body weight was 10.70 ± 2.00% higher than those in the model group, and the fasting blood glucose (FBG), AUC of the oral glucose tolerance test, and insulin sensitivity test values were 73.23 ± 3.33%, 12.31 ± 2.29%, and 13.61 ± 5.60% lower in the RRE group, respectively. When compared with the model group, an increase of 45.76 ± 3.03% in the glucose uptake of HepG2 cells with IR was seen in the RRE group. The drug (RR)-components-disease (DM)-targets network with 18 components and 58 targets was established. 331 differentially expressed genes (DEGs) were identified. TRPV1 and SCD1 were important DEGs by the intersectional analysis of network pharmacology and renal transcriptome. The TRPV1 overexpression significantly inhibited apoptosis and oxidative stress of the HK2 cells induced by HG, while SCD1 overexpression induced apoptosis and oxidative stress of the HK2 cells induced by low and high glucose. When compared to the HG group, the mRNA and protein expressions of TRPV1 in the presence of RRE (100 μg/ml) increased by 3.94 ± 0.08 and 2.83 ± 0.40 folds, respectively.Conclusion: In summary, RR displayed an inspiring antidiabetic effect by reducing FBG and IR, upregulating the mRNA and protein expressions of TRPV1, and downregulating mRNA expression of SCD1. Induction of TRPV1 and inhibition of SCD1 by RR was possibly one of its antidiabetic mechanisms.